Circular RNA hsa_Circ_0007552 inhibits lung adenocarcinoma proliferation, migration and invasion via the miR-7974/BAP1 axis - Lin, Yanping; Li, Rong; Shen, Xin; Wu, Mingjin; Tang, Jiadai; Guo, Jiangyan; Yin, Caixin; Xia, Tingrong; Li, Dongqi; Hu, Fengdi; Liao, Yedan; Li, Rui; et al. (Frontiers in Immunology, 2025)
ObjectivesCircular RNAs (circRNAs) are a class of non-coding RNAs with diverse pathophysiological functions. However, the functional roles and molecular mechanisms of circRNAs in lung adenocarcinoma (LUAD) remain to be further elucidated.MethodsThe expression levels of Circ_0007552 (Circ_RILPL1), miR-7974, and BRCA1-associated protein 1 (BAP1) mRNA in LUAD tissues and cells were detected by quantitative real-time PCR (qRT-PCR). Cell viability, migration, and invasion capabilities were evaluated using the Cell Counting Kit-8 (CCK-8), colony formation assay, wound healing assay, and Transwell migration and invasion assays. A xenograft tumor model in nude mice was established to assess the in vivo effects of Circ_0007552 on LUAD by measuring tumor size, weight, and growth rate. Bioinformatics analysis and dual-luciferase reporter gene assays were conducted to validate the interactions among Circ_0007552, miR-7974, and BAP1. Western blot was performed to detect the protein expression of BAP1.ResultsCirc_0007552 exhibited low expression in LUAD tissues and cells, correlating with clinicopathological features such as tumor size, lymph node metastasis, clinical stage, and poor prognosis. Both in vitro and in vivo experiments demonstrated that Circ_0007552 overexpression suppressed malignant biological behaviors of LUAD cells, whereas its knockdown exerted opposite effects. Mechanistically, Circ_0007552 functioned as a competing endogenous RNA (ceRNA) for miR-7974, negatively regulating its expression. Overexpression of miR-7974 partially reversed the tumor-suppressive effects of Circ_0007552 on LUAD cells. Furthermore, BAP1 was identified as a downstream target of miR-7974, and Circ_0007552 positively modulated BAP1 expression.ConclusionCirc_0007552 inhibits the development, progression, and metastasis of lung cancer by sponging miR-7974 to upregulate BAP1 expression. The present study further elucidates the underlying molecular mechanisms driving lung cancer progression.